Is colonoscopic surveillance reducing colorectal cancer mortality in ulcerative colitis? A population based case control study. Issue 5 (1st May 1998) - Karlén, P; Kornfeld, D; Broström, O; Löfberg, R; Persson, P-G; Ekbom, A
Abstract : Background —Colonoscopic surveillance is a standard procedure in many patients with long standing, extensive ulcerative colitis (UC), in order to avoid death from colorectal cancer. No conclusive proof of its benefits has been presented however. Aims —To evaluate the association between colonoscopic surveillance and colorectal cancer mortality in patients with UC. Patients —A population based, nested case control study comprising 142 patients with a definite UC diagnosis, derived from a study population of 4664 patients with UC, was conducted. Methods —Colonoscopic surveillance in all patients with UC who had died from colorectal cancer after 1975 was compared with that in controls matched for age, sex, extent, and duration of the disease. Information on colonoscopic surveillance was obtained from the medical records. Results —Two of 40 patients with UC and 18 of 102 controls had undergone at least one surveillance colonoscopy (relative risk (RR) 0.29, 95% confidence interval 0.06 to 1.31). Twelve controls but only one patient with UC had undergone two or more surveillance colonoscopies (RR 0.22, 95% confidence interval 0.03 to 1.74), indicating a protective dose response relation. Conclusion —Colonoscopic surveillance may be associated with a decreased risk of death from colorectal cancer in patients with long standing UC.